Deep medullary veins are associated with widespread brain structural abnormalities. Issue 6 (June 2022) - Liu, Zi-Yue; Zhai, Fei-Fei; Ao, Dong-Hui; Han, Fei; Li, Ming-Li; Zhou, Lixin; Ni, Jun; Yao, Ming; Zhang, Shu-Yang; Cui, Li-Ying; Jin, Zheng-Yu; Zhu, Yi-Cheng
Our aim is to investigate the association of cerebral deep medullary veins (DMVs) with white matter microstructural integrity and regional brain atrophy in MRI. In a community-based cohort of 979 participants (mean age 55.4 years), DMVs were identified on susceptibility-weighted imaging. Brain structural measurements including gray matter and hippocampus volumes, as well as diffusion tensor metrics, were evaluated. The mean (SD)number of DMVs was 19.0 (1.7). A fewer number of DMVs was related to lower fractional anisotropy and higher mean diffusivity in multiple voxels on the white matter skeleton (threshold-free cluster enhancement corrected p < 0.05, adjusted for age and sex). Also, fewer DMVs were significantly related to a lower gray matter fraction and a hippocampal fraction (0.10 and 0.11 per DMV, respectively; SE, 0.03 for both; p < 0.001 for both). A significant correlation between DMVs' reduction and cortical atrophy was observed in the bilateral occipital lobes, temporal lobes, hippocampus, and frontal lobes (p < 0.001, adjusted for age, sex, and total intracranial volume). Our results provided evidence that cerebral small venules disease play a role in brain parenchymal lesions and neurodegenerative processes.